2017
DOI: 10.1016/j.drugpo.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Legal cannabis laws, home cultivation, and use of edible cannabis products: A growing relationship?

Abstract: Background Over half of U.S. states have enacted legal cannabis laws (LCL). In parallel, edible cannabis products (i.e., edibles) have presented new regulatory challenges. LCL provisions that dictate access to cannabis (e.g., home cultivation (HC) or dispensaries (DSP)) may impact edible production and use. This study examined relationships among HC and DSP provisions, cannabis cultivation, and edible use. Methods An online cannabis use survey was distributed using Facebook. Data were collected from 1813 can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 48 publications
2
18
0
1
Order By: Relevance
“…At that point, we have increased the amount of money spent to anywhere between US $30 and US $60 per day. Figure 1 displays the Facebook advertisement click results from our most recently published survey [ 57 ]. In this study, we preprogrammed advertisements to be displayed for 6 days (September 3-8, 2016).…”
Section: Using the Facebook Advertising Platformmentioning
confidence: 99%
See 2 more Smart Citations
“…At that point, we have increased the amount of money spent to anywhere between US $30 and US $60 per day. Figure 1 displays the Facebook advertisement click results from our most recently published survey [ 57 ]. In this study, we preprogrammed advertisements to be displayed for 6 days (September 3-8, 2016).…”
Section: Using the Facebook Advertising Platformmentioning
confidence: 99%
“…We have conducted a series of Web surveys using these methods, which have provided insights into patterns of cannabis use across the United States. Below we present data from 6 of those surveys, 3 of which have been published [ 57 , 59 , 60 ]. Table 1 provides an overview of the recruitment results for each of the surveys.…”
Section: Cannabis-related Findings From Facebook Advertising–generatementioning
confidence: 99%
See 1 more Smart Citation
“…regarding accidental cannabis ingestion by children (Barrus et al, 2016;McGill, 2014). A recent survey by Borodovsky and Budney (2017) found that respondents who lived in a state where home cultivation was legal had a greater likelihood of both growing cannabis and preparing homemade edibles. Given the large amount of interest among respondents in this study in both trying edibles and in preparing them at home, there may be a greater incidence of accidental ingestion by adults and children, as observed elsewhere following cannabis legalization.…”
Section: Demographic Variable Number Of Respondents (%)mentioning
confidence: 99%
“…Odobrenje Ministarstva zdravlja po pravilu dolazi u obzir samo ako su ispunjeni precizno propisani "uslovi/simptomi i ako su iscrpljene druge, ‚konvencionalne' terapeutske opcije" (Sznitman, Lewis, 2018: 219). 3 Dozvolom Ministarstva zdravlja se utvrđuju mesečna doza koju pacijent može uzimati (po pravilu između 20 i 100 grama), dobavljač kanabisa i period trajanja dozvole (dozvole su oročene na šest meseci i mogu se obnavljati na zahtev lekara specijaliste) (Sznitman, Lewis, 2015: 447). U Izraelu i širom sveta je otvorena rasprava o eventualnim štetnim posledicama medicinske upotrebe kanabisa.…”
Section: Legalizacija Medicinske Upotrebe Kanabisaunclassified